Algae optical density sensor for pond monitoring and production process control - Yao, Yao; Ge, Yufeng; Thomasson, J. Alex; Sui, Ruixiu (International Journal of Agricultural and Biological Engineering, 2018)
Open raceways are one of the principal commercial-scale systems for cultivating algae to produce biofuels and bioproducts. A critical process parameter in such a system is algae cell concentration in the aqueous culture, commonly measured in terms of optical density (OD). A prototype OD sensor exclusively for real-time measurement of algae cell concentration in open ponds was designed, constructed, and tested in a laboratory scale raceway and an open-pond raceway. In the lab test, the sensor OD measurements were highly correlated with spectrometer OD measurements. The OD curve recorded by the sensor clearly showed the diurnal pattern of algae growth associated with the on-off cycle of the lighting system in the lab facility. The test data also clearly highlighted unique cultivation activities such as growth media addition and harvesting. In the open pond raceway test, sensor OD data were also highly correlated with spectrometer-measured OD even though the range of OD variation was significantly less during this test. The OD curve clearly indicated a higher biomass accumulation rate in the pond from late morning to late afternoon than during the rest of the day. These tests of the OD sensor demonstrated its potential to provide accurate real-time algae concentration data in an open pond cultivation system, the type of data that would be necessary for timely management decision-making. This sensor would also eliminate the cost associated with frequently collecting and analyzing samples, making commercial-scale algae production more economically practical. Keywords: microalgae, optical density (OD), open pond raceway, sensor, pond monitoring, circuit design, optoelectronics DOI: 10.25165/j.ijabe.20181101.2839 Citation: Yao Y, Ge Y F, Thomasson J A, Sui R X. Algae optical density sensor for pond monitoring and production process control. Int J Agric & Biol Eng, 2018; 11(1): 212–217.